2007
DOI: 10.1038/sj.npp.1301273
|View full text |Cite
|
Sign up to set email alerts
|

The Abused Inhalant Toluene Increases Dopamine Release in the Nucleus Accumbens by Directly Stimulating Ventral Tegmental Area Neurons

Abstract: Recreational abuse of toluene-containing volatile inhalants by adolescents is a significant public health problem. The mechanisms underlying the abuse potential of such substances remain unclear, but could involve increased activity in mesoaccumbal dopamine (DA) afferents innervating the nucleus accumbens (ACB). Here, using in vitro electrophysiology, we show that application of behaviorally relevant concentrations of toluene directly stimulates DA neurons in the ventral tegmental area (VTA), but not surroundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 89 publications
3
63
0
Order By: Relevance
“…In line with this idea, it has been demonstrated that toluene exposure increases dopamine release and dopaminergic neuron activity in the mesolimbic system [24,45]. The sensitization theory of addiction [46,47] suggests that an increase in locomotor activity can predict reinforcing drug effects and addiction liability.…”
Section: Locomotor Effectsmentioning
confidence: 89%
“…In line with this idea, it has been demonstrated that toluene exposure increases dopamine release and dopaminergic neuron activity in the mesolimbic system [24,45]. The sensitization theory of addiction [46,47] suggests that an increase in locomotor activity can predict reinforcing drug effects and addiction liability.…”
Section: Locomotor Effectsmentioning
confidence: 89%
“…For example, brief (1-15 min) exposures to 11,500 ppm toluene produce a transient increase in neuronal firing in the ventral tegmental area (VTA) [Riegel and French 1999a;1999b;Riegel et al 2007]. Like cocaine, toluene increases extracellular dopamine levels in the prefrontal neocortex [Gerasimov et al 2002b] and nucleus accumbens [Riegel et al 2007].…”
Section: Neuropharmacological Bases Of Toluene Abusementioning
confidence: 99%
“…For example, brief (1-15 min) exposures to 11,500 ppm toluene produce a transient increase in neuronal firing in the ventral tegmental area (VTA) [Riegel and French 1999a;1999b;Riegel et al 2007]. Like cocaine, toluene increases extracellular dopamine levels in the prefrontal neocortex [Gerasimov et al 2002b] and nucleus accumbens [Riegel et al 2007]. Another study found that toluene alone did not increase dopamine levels in the nucleus accumbens, but did greatly exacerbate the increase caused by cocaine [Beyer et al 2001;Gerasimov et al 2002a;Riegel et al 2003].…”
Section: Neuropharmacological Bases Of Toluene Abusementioning
confidence: 99%
“…Increased toluene-induced locomotor activity can be attenuated by pre-treatment with remoxipride, a dopamine D 2 receptor antagonist (19) suggesting that this hyperactivity is mediated via dopamine-dependent mechanisms. These observations have been refined illustrating that toluene's effects can be attributed to time dependent increases in the action potential drive of VTA neurons which enhances dopamine release at projection sites (20). Furthermore the magnitude of firing does not decline following prolonged exposure (20), leading to persistent dopaminergic dysfunction.…”
Section: The Effects Of Inhalants On the Dopaminergic Systemmentioning
confidence: 96%